Adaptative Divergence of Cryptococcus neoformans: Phenetic and Metabolomic Profiles Reveal Distinct Pathways of Virulence and Resistance in Clinical vs. Environmental Isolates - Camila Botelho Miguel; Geovana Pina Vilela; Lara Mamede Almeida; Mariane Andrade Moreira; Glicélia Pereira Silva; Jamil Miguel-Neto; Melissa Carvalho Martins-de-Abreu; Ferdinando Agostinho; Javier Emilio Lazo-Chica; Mariana Santos Cardoso; Siomar de Castro Soares; Aristóteles Góes-Neto; et al. (Journal of Fungi)
Cryptococcus neoformans is a life-threatening fungal pathogen that primarily affects immunocompromised individuals. While antiretroviral therapy has reduced incidence in developed nations, fluconazole-resistant strains and virulent environmental isolates continue to pose challenges, especially because they have many mechanisms of adaptability, supporting their survival. This study explores the phenetic and metabolomic adaptations of C. neoformans in clinical and environmental contexts to understand the factors influencing pathogenicity and resistance. Methods: An in silico observational study was conducted with 16 C. neoformans isolates (6 clinical, 9 environmental, and 1 reference) from the NCBI database. Molecular phenetic analysis used MEGA version 11.0.13 and focused on efflux pump protein sequences. Molecular phenetic relationships were assessed via the UPGMA clustering method with 1000 bootstrap replicates. The enzymatic profiling of glycolytic pathways was conducted with dbCAN, and metabolomic pathway enrichment analysis was performed in MetaboAnalyst 6.0 using the KEGG pathway database. Results: Molecular phenetic analysis revealed distinct clustering patterns among isolates, reflecting adaptations associated with clinical and environmental niches. Clinical isolates demonstrated enriched sulfur metabolism and glutathione pathways, likely adaptations to oxidative stress in host environments, while environmental isolates favored methane and glyoxylate pathways, suggesting adaptations for survival in carbon-rich environments. Conclusion: Significant phenetic and metabolomic distinctions between isolates reveal adaptive strategies for enhancing virulence and antifungal resistance, highlighting potential therapeutic targets.